2016
DOI: 10.1080/02652048.2016.1234513
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, in vitro evaluation and kinetic analysis of chitosan–gelatin bilayer muco-adhesive buccal patches of insulin nanoparticles

Abstract: The present study was performed to optimise the formulation of a muco-adhesive buccal patch for insulin nanoparticles (NPs) delivery. Insulin NPs were synthesised by an ionic gelation technique using N-di methyl ethyl chitosan cysteine (DMEC-Cys) as permeation enhancer biopolymer, tripolyphosphate (TPP) and insulin. Buccal patches were developed by solvent-casting technique using chitosan and gelatine as muco-adhesive polymers. Optimised patches were embedded with 3 mg of insulin-loaded NPs with a homogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The film was put on the upper side of the disc, together with the disc, immersed in the dissolution vessel [28,42,43]. Samples of 4 mL were taken from the medium at fixed time intervals (5, 10, 15, 30, 45, 60 min) and replaced with a fresh dissolution medium [44]. All samples were filtered through a 0.45 μm membrane filter (Millipore, Bedford, MA, USA).…”
Section: In Vitro Drug Release Studiesmentioning
confidence: 99%
“…The film was put on the upper side of the disc, together with the disc, immersed in the dissolution vessel [28,42,43]. Samples of 4 mL were taken from the medium at fixed time intervals (5, 10, 15, 30, 45, 60 min) and replaced with a fresh dissolution medium [44]. All samples were filtered through a 0.45 μm membrane filter (Millipore, Bedford, MA, USA).…”
Section: In Vitro Drug Release Studiesmentioning
confidence: 99%
“…In this study, the fitted result using the Korsmeyer-Peppas model was M t /M ∞ = 0.083 t 0.958 (R 2 = 0.988) for the drug release. Therefore, the n value was 0.958, which indicates the mechanism of anomalous diffusion and that the drug release of Gos-GFTs may have been regulated by the joint action of erosion and diffusion ( Acharya et al, 2014 , Mahdizadeh Barzoki et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticulate dosage forms differ from conventional dosage forms by loading the drug or active compound into nanoparticles prior to dispersion in a formulation base. They have been incorporated into various dosage forms for sublingual and buccal drug delivery, including gels (Marques et al, 2017), sprays (Baltzley et al, 2018), tablets (Gavin et al, 2015; El-Nahas et al, 2017), films (Giovino et al, 2013; Mortazavian et al, 2014; Al-Dhubiab et al, 2016; Masek et al, 2017; Castro et al, 2018a; Mahdizadeh Barzoki et al, 2018; Al-Nemrawi et al, 2019), and patches (Mahdizadeh Barzoki et al, 2016). These nanoparticulate formulations have been shown to: (i) improve drug permeability across the epithelium; (ii) modify drug release kinetics (e.g., controlled release or sustained release); (iii) provide solubilization (i.e., to deliver compounds which have physicochemical properties that strongly limit their aqueous solubility); and/or (iv) protect compounds that are sensitive to degradation (e.g., peptides) (Morales and Brayden, 2017; Hua et al, 2018).…”
Section: Nanoparticulate Drug Delivery Approachesmentioning
confidence: 99%
“…The majority of the studies have demonstrated sustained drug release from the nanoparticles embedded in the dosage form, with the drug then being diffused into the formulation base and absorbed into the adhered mucosa. These include nanoparticles incorporated into gels (Marques et al, 2017), sprays (Baltzley et al, 2018), tablets (Gavin et al, 2015; El-Nahas et al, 2017), films (Giovino et al, 2013; Mazzarino et al, 2014; Mortazavian et al, 2014; Al-Dhubiab et al, 2016; Masek et al, 2017; Castro et al, 2018a; Mahdizadeh Barzoki et al, 2018; Al-Nemrawi et al, 2019), and patches (Mahdizadeh Barzoki et al, 2016). Very few studies have demonstrated release of nanoparticles from the formulation base and mucosal penetration of intact nanoparticles for drug delivery (Mortazavian et al, 2014; Masek et al, 2017).…”
Section: Nanoparticulate Drug Delivery Approachesmentioning
confidence: 99%